PENGARUH KUALITAS LAYANAN DAN KOMPETENSI DOSEN TERHADAP KEPUASAN MAHASISWA (The Effect of Service Quality and Lecturer Competence on Student Satisfaction) - Muh. Fauzi Marzuki; Nurwati Nurwati; Nursaban Rommy (Pascasarjana Universitas Halu Oleo, 2019)
The objectives of this study are: (1) To find out the Effect of Service Quality on Student Satisfaction at Avicenna's STIK (High School of Health Sciences) Kendari; (2) To determine the effect of lecturer competence on student satisfaction at the Avicenna Kendari Institute of Health Sciences (STIK); (3) To find out the Effect of Service Quality and Lecturer Competence on Student Satisfaction in Avicenna's STIK (College of Health Sciences) Kendari. Population in this study were all Avicenna Kendari students of STIK (College of Health Sciences) Avicenna Kendari class of 2015, 2016 and 2017 registered on 2017/2018 school year totaling 446 people. The sample in this study was 211 respondents using the Slovin method. The type of data used in this study are primary data and secondary data. The data analysis method used in this research is descriptive analysis and inferential statistics, namely Multiple Linear Regression. The results of the study stated that: (1) Service quality has a significant effect on student satisfaction at Avicenna's STIK (High School of Health Sciences) Kendari; (2) Lecturer competence has a significant effect on student satisfaction at the Avicenna Kendari School of Health Sciences (STIK); (3) Service quality and lecturer competence have a significant effect on student satisfaction at Avicenna Kendari Institute of Health Sciences